1001Spatio-temporal epidemiology of mumps and related region factors in Korea. (2nd September 2021) - Hong, Kwan; Hwang, Hari; Chun, Byung Chul
Abstract: Background: Mumps is in Korea's national immunization program, though there are still epidemics, especially in young age. The study's objectives are to establish the epidemiological characteristics of mumps and suggest the predicting factors. Methods: We extracted cases from national health insurance data, between 2013 and 2017. Age-specific incidence rate and geographical distribution were evaluated. We tested for spatial autocorrelation by Moran's I statistics with Delaunary triangular links. Simultaneous autoregressive model for cumulative incidence of mumps using triangular links was used to predict cumulative incidence with region specific factors. Results: A total of 219, 149 (85.12 per 100, 000) were diagnosed and 23, 805 (9.25 per 100, 000) were hospitalized. Weekly cumulative incidence showed two epidemics every year, between weeks 20-25 and 40-45. Cumulative incidence of ages 10-19 was the highest, 332.21 per 100, 000 people, followed by 300.75 per 100, 000 people in ages 0-9. Geographical distribution showed clusters of epidemics, and Moran's I statistics was 0.304 with a p-value <0.01. The Simultaneous autoregressive model estimated the mean age and hospital resources of each region as prediction factors for geographical distribution of mumps. Conclusions: Mumps is common in children and peaks in summer and winter. Additionally, there are geographical clusters in epidemics, and the effect of region factors such as mean age and hospital resources are suspected. Key messages: Two peaks in age and season appear in mumps in Korea. Clusters of geographical distribution indicate that region factors may affect the incidence.